Bus terminal architecture for sustainable transportation in Nigeria: an overview of the challenges - Sani, Sambo Zainab; Shah, Muhammad Zaly; Bayero, Salih Fara (Universiti Teknologi MARA, Perak, 2025)
An effective transportation system is primarily attributable to well-designed terminal architecture. It has been established that poor terminal structure hindered commuters’ patronage, especially people with disabilities. The arrangement and quality of services provided at the terminal, which encompasses all terminal user categories, determine the degree of patronage from commuters. As considered one of the most important sustainable transportation, the development of adequate road terminals has been thriving over the last decade, especially in the densely populated cities of Nigeria. This paper explores the impact of Nigeria's road terminal on achieving a sustainable transport system. The methodology employed information gathering from literature and different bus terminals in Nigeria. The results of the empirical study confirmed that service quality can be conceptualized as functional service quality, technical service quality, comfort and cleanness, and service planning and reliability. It has positive effects on reuse intention by enhancing customer satisfaction, as customer satisfaction has an intermediary effect on passengers' repurchase intention. This study contributes to transport agencies analysing the relationship between service quality attributes and passengers’ reuse intention for improving the supplied service, increasing ridership, and implementing the sustainable transport policy.